Identification of SP1683 as a pneumococcal protein that is protective against nasopharyngeal colonization - Leen Moens; Philippe Hermand; Tine Wellens; Greet Wuyts; Rita Derua; Etienne Waelkens; Carine Ysebaert; Fabrice Godfroid; Xavier Bossuyt (Taylor & Francis Group, 2018)
Serotype-independent protein-based pneumococcal vaccines represent attractive alternatives to capsular polysaccharide-based vaccines. The aim of this study was to identify novel immunogenic proteins from Streptococcus pneumoniae that may be used in protein-based pneumococcal vaccine. An immunoproteomics approach and a humanized severe combined immunodeficient mouse model were used to identify S. pneumoniae proteins that are immunogenic for the human immune system. Among the several proteins identified, SP1683 was selected, recombinantly produced, and infection and colonization murine models were used to evaluate the capacity of SP1683 to elicit protective responses, in comparison to known pneumococcal immunogenic proteins (PhtD and detoxified pneumolysin, dPly). Immunisation with SP1683 elicited a weaker antibody response than immunisation with PhtD and did not provide protection in the model of invasive disease. However, similar to PhtD, it was able to significantly reduce colonization in the mouse model of nasopharyngeal carriage. Treatment with anti-IL17A and anti-IL17F antibodies abolished the protection against colonization elicited by SP1683 or PhtD + dPly, which indicated that the protection afforded in this model was Th17-dependent. In conclusion, intranasal immunization with the pneumococcal protein SP1683 conferred IL17-dependent protection against nasopharyngeal carriage in mice, but systemic immunization did not protect against invasive disease. These results do not support the use of SP1683 as an isolated pneumococcal vaccine antigen. Nevertheless, SP1683 could be used as a first line of defence in formulations combining several proteins.